Cobalt(II)‐Catalyzed [4+2] Annulation of Picolinamides with Alkynes via C−H Bond Activation. Issue 25 (17th April 2020) - Yao, Yongqi; Lin, Qifu; Yang, Wen; Yang, Weitao; Gu, Fenglong; Guo, Wei; Yang, Dingqiao
Abstract: A cobalt(II)‐catalyzed [4+2] annulation of picolinamides with alkynes via C−H bond activation has been developed. The operationally simple annulation reaction allows for the synthesis of acyl‐substituted 1 H ‐benzoquinoline bearing multiple aromatic rings (up to 96 % yield) without co‐oxidant or other oxidation factors under mild conditions. Several control experiments were carried out. This practical [4+2] annulation provides an efficient route to access highly functionalized compounds. Abstract : Free from any oxidation factor : A co‐oxidant free cobalt(II)‐catalyzed picolinamide‐directed annulation of alkyne via C(sp 2 )−H bond activation was developed. Under the optimized reaction condition, the reaction system shows a wide scope of alkynes and obtains the novel annulation acyl‐substituted 1 H ‐benzoquinoline in good to excellent yields (up to 96 %).